Spatial Heterogeneity of Rice Production Responses to ENSO Anomalies in Banten Province, Indonesia - Tian Mulyaqin; Rita Nurmalina; Nunung Kusnadi; Bambang Hendro Trisasongko (Green Engineering Society, 2026)
El Niño–Southern Oscillation (ENSO) anomalies are significant drivers of climate variability affecting agricultural production, although their impacts exhibit high spatial and temporal complexity. This study investigates rice production responses to ENSO phases in four districts of Banten Province, Indonesia—Pandeglang, Serang, Lebak, and Tangerang—during the 2000–2024 period. Utilizing descriptive statistics, OLS regression, and comparative time-series models (linear, quadratic, exponential, and moving average), the study evaluates how climatic signals are translated into production outcomes. Results reveal significant spatial heterogeneity. Although El Niño generally suppressed yields, regression analysis identifies Tangerang as the only district with a statistically significant vulnerability to drought-induced losses (β= -33,371 t/year). Conversely, the study identifies a